Hasil Belajar Pada Mahasiswa Pendidikan Olahraga Dan Kesehatan: Study Korelasional antara Persepsi, Sikap Mahasiswa Dan Motivasi Belajar - Onny Siagian, Ade (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2021)
The purpose of the study. Determine the relationship between in perceptions, attitudes and learning motivation to learning outcomes, considering that many students have not obtained good learning achievement. There are two factors that influence learning outcomes, namely external factors and internal factors. Internal factors are student perceptions, student attitudes, and learning motivation. Materials and methods. This type of quantitative research uses correlational analysis techniques, the population of this study is all students of the 2019 PORKES Study Program which can be 140 people, while the sample in this study is 72 people. In this study, the sampling technique used proportional random sampling technique. The instruments used were the perception questionnaire, the attitude questionnaire and the learning motivation questionnaire. Data obtained from simple message and simple regression for hypothesis one, two and three without permission from multiple regression. Results. The results of the data analysis show that: (1) there is a significant relationship between student perceptions and learning outcomes of Porkes Indraprasta University students, (2) there is no significant relationship between student attitudes towards student learning outcomes of PORKES UNINDRA, (3) student learning motivation towards student learning outcomes PORKES UNINDRA, (4) there is no significant relationship between student perceptions, student attitudes, and student learning motivation together on student learning outcomes PORKES UNINDRA. Conclusions. This study it can be concluded that student perceptions, student attitudes, and student motivation to learn significantly contribute to student learning outcomes PORKES UNINDRA.